Differential expression of mucin in salivary gland tumours / Nurul Inaas Mahamad Apandi - Nurul Inaas, Mahamad Apandi (2020)
Introduction: Varied alterations in types of secreted mucin may affect the regulation of cell growth, immune response and adhesion of cell. These changes may indirectly contribute to the ability of tumour invasion and metastasis. However, the expression of mucins in salivary gland tumours has not been explored in depth. Objectives: To investigate expressions of mucin in the salivary gland tumour microenvironment and make comparisons between benign and malignant, and minor and major salivary gland tumours. Methods: Special stains were used to stain neutral mucin (Periodic acid Schiff), sialomucin (Alcian Blue) and sulfomucin (Aldehyde Fuschin) within tissues from 6 normal salivary glands and salivary gland tumours including 31 pleomorphic adenoma (PA), 27 mucoepidermoid carcinoma (MEC) and 15 adenoid cystic carcinoma (AdCC). Statistical analyses to compare mucin expression in these salivary gland tumours were done using Chi-square tests. Results: Sialomucin was the most expressed mucin in all salivary gland tumours regardless of origin. A significant difference was observed in mucin expression between benign and malignant salivary gland tumours, in which PA showed 3 times significantly higher expression of sialomucin compared to MEC and AdCC (p=0.028). PAs of major gland origin showed 42 times significantly higher expression of sialomucin compared to PAs of minor gland (p=0.000). Conclusion: Alcian blue was the best special stain to visualize mucin elements in salivary gland tumours. Sialomucin content in PA of major glands was vastly increased from that in minor glands. The degree of sialomucin expression may play a role in diagnosis of borderline salivary gland tumours.